Analisis Dampak Pandemi Covid 19 Terhadap Pendapatan UMKM (Studi Kasus Home Industri Payung Tedung Kebudayaan Bali di Lampung Tengah Seputih Raman) - I Kadek Peby Diana; Rosmiati Tarmizi (Jurnal EMT KITA, 2023)
The Covid-19 pandemic has greatly affected many countries, including Indonesia in 2020. As an infectious disease that attacks the respiratory system, Covid-19 has put great pressure on micro businesses, small and medium-sized enterprises (MSMEs), especially in the wake of the Covid-19 emergency. forced. This study focuses on the Balinese cultural umbrella industry in Seputih Raman, Central Lampung, which has seen significant changes during the pandemic. Qualitative methods were used with interviews and direct observations of business owners. The results of the study show that the income of Bali's culturally peak MSMEs has dropped significantly during the pandemic period due to travel restrictions and reduced tourism activities. Faced with the post-pandemic situation, Bali cultural patronage MSMEs need to adjust their business strategies, look for new opportunities and increase their competitiveness. Government support and cooperation with stakeholders is seen as vital to support future recovery and growth of the MSME sector.